Profile of pregnant women with tuberculosis at the tuberculosis policlinic of the eradication of tuberculosis, Tuberculosis Foundation, Baladewa Central Jakarta - Maharani, Laksmi (Indonesian Journal of Obstetrics and Gynecology, 2009)
Objective: To know profile of pregnant women with tuberculosis at PPTI Baladewa polyclinic Jakarta, to evaluate impacts of tuberculosis medicinal treatment on pregnancy and to know the obstacles of pregnant women to look for tuberculosis treatment. Methods: Subjects were all pregnant women with tuberculosis and received tuberculosis treatment at polyclinic of PPTI Baladewa from January 2006 - December 2007. We reviewed medical record and did home visitation to fill questioners. Results: All subjects were in reproductive age and most of all were low socio-economic group. Pulmonary tuberculosis was found in 88.2% cases and Extrapulmonary tuberculosis in 11.8% cases. We found 29.4% relapse cases and 11.8% multi-drug resistance. Sputum examination with a smear positive for acid fast-bacillus was found in 52.9% cases. There was abnormality for all chest x-rays. The third most frequently symptoms were cough more than two weeks (88.2%), weight loss (88.2%) and anorexia (82.4%). Average time for the patients to look for treatment was 50.71 Â± 31.2 days. The patients need more time because most of the symptoms are also present in pregnancy, the patients know absolutely nothing about TB and healthcare provider didnât examine carefully. Treatment for the patients was given immediately without considering the gestational age. Conclusion: No harmful effect was observed for neonates even if the drugs were given in the first trimester of pregnancy. [Indones J Obstet Gynecol 2009;33-4:210-5] Keywords: profile, pregnancy, tuberculosis